Effect of extracts of two aquatic plants Typha domingensis (Pers), and Lemna minor (Lamarc) on Ecophysiology of common carp Cyprinus carpio (Linnaeus) - Talal, Abdul Majeed H.; Haraib, Khadijah K. (Iraqi Journal of Aquaculture, 2022)
This study aimed at investigating the impacts of aquatic extracts of two macrophytes Typha domingensis (Pers) and Lemna minor(Lamarc) on the Ecophysiology of the common carp Cyprinus carpio (Linnaeus) reared in waste water. A total of eighty fish were divided into four groups, each group consists of ten fish. Four treatment were used with two replicates of they were made as follow; waste water, clean water (control), waste water- extract of T. domingensis and waste water- extract of L. minor. Healthy freshwater common carp weighing about 35.75 ± 0.60g were obtained from the aquaculture station of Marine Science Centre /University of Basrah. Physicochemical properties of waters used were recorded and controlled. The diet given to waste water–aquatic plant extract groups was mixed for one night. Blood smears were taken. White blood cells/1 mm3 were counted by using Neubaur Improved Haemocytometer and light compound microscope. The results indicated that the number of white blood cells of common carp for the control sample was more than that of waste water. While the numbers of white blood cells of the fish in separately treated waste water with T. domingensis and L. minor extracts were close to the number of the control sample. Blood smears of fish reared in clean water (control sample), waste water- T. domingensis extract and waste water- L. inor extract seemed quite normal, where as the smear of the blood of fish reared in waste water showed abnormalities in the blood such as disruption of cell walls and deformation of the shape of red blood cell.